Extradural Dermoid Cyst of the Anterior Infratemporal Fossa. Case Report - Watanabe, Kentaro; Filomena, Carol A.; Nonaka, Yoichi; Matsuda, Masahide; Zomorodi, Ali R.; Friedman, Allan H.; Fukushima, Takanori (Journal of Neurological Surgery Reports, 2015)
Dermoid cysts are rare in the skull base. There have been 10 reported cases of dermoid cysts in the cavernous sinus, two in the petrous apex, and one in the extradural Meckel cave. This is the first case report of a dermoid cyst in the anterior infratemporal fossa attached to the anterior dura of the foramen ovale. The clinical presentation, radiologic findings, histologic features, tumor origin, and operative technique are described along with a review of the literature.
Keywords: dermoid cyst; anterior infratemporal fossa; extradural